Does Mindfulness Training Without Explicit Ethics-Based Instruction Promote Prosocial Behaviors? A Meta-Analysis. (August 2020) - Berry, Daniel R.; Hoerr, Jonathan P.; Cesko, Selena; Alayoubi, Amir; Carpio, Kevin; Zirzow, Hannah; Walters, Wesley; Scram, Genny; Rodriguez, Katie; Beaver, Vanessa
Scholarly discourse has raised concerns about the gravitas of secular mindfulness trainings in promoting prosocial outgrowths, as these trainings lack ethics-based concepts found in contemplative traditions. Random-effects meta-analyses were conducted to test whether mindfulness trainings absent explicit ethics-based instructions promote prosocial action. There was a range of small to medium standardized mean difference effect sizes of mindfulness training on overt acts of prosociality when compared with active and inactive controls, k = 29, N = 3, 100, g = .426, 95% confidence interval (CI)( g ) = [.304, .549]. Reliable effect size estimates were found for single-session interventions that measured prosocial behavior immediately after training. Mindfulness training also reliably promotes compassionate (but not instrumental or generous) helping and reliably reduces prejudice and retaliation. Publication bias analyses indicated that the reliability of these findings was not wholly dependent on selective reporting. Implications for the science of secular mindfulness training on prosocial action are discussed.